Nanoparticles as carriers for drug delivery in cancer. (5th November 2018) - Dadwal, Ankita; Baldi, Ashish; Kumar Narang, Raj
Abstract: Cancer nanotherapeutics are swiftly progressing and are being applied to solve several limitations of conventional drug delivery systems such as non-specific biodistribution and targeting, lack of water solubility and poor oral bioavailability. Advances in protein engineering and materials science have contributed to novel nanoscale targeting approaches that may bring new hope to cancer patients. Several therapeutic nanocarriers have been approved for clinical use. Nanoparticles have been designed for optimal size and surface characteristics to improve their biodistribution and to increase their circulation time in the bloodstream. By selectively using the unique pathophysiology of tumours, such as their enhanced permeability and retention effect nanotherapeutics are able to carry loaded active drug to cancer cells. In addition to this passive targeting mechanism, active targeting strategies using ligands or antibodies directed against selected tumour targets magnify the specificity of these therapeutic nanoparticles. Drug resistance, another obstacle can also be overcome or reduced by using nanoparticles. Multifunctional and multiplex nanoparticles are now being actively investigated and are on the horizon as the next generation of nanoparticles, facilitating personalized and tailored cancer treatment.